Pendampingan Administrasi Perpajakan Bagi Anggota Organisasi Sosial di Desa Muara Penimbung Ulu - Muhammad Hidayat; Sri Maryati; Ery Erman; Winda Kurnia Sari (Sriwijaya Accounting Community Services, 2024)
Taxes are the main source of state income. Taxpayer compliance is the key to the success of a country's development. Tax administration management assistance is needed not only by employees, but also by members of social organizations. The aim of this assistance is to increase public awareness of orderly tax administration, especially for the people in Muara Penimbung Ulu Village.